Adsorption of Phenol from Aqueous Solution Using Activated Carbon prepared from Coconut Shell - Ripa, Masuma Sultana; Mahmood, Rafat; Khan, Sabrina; Khan, Easir A (Journal of Chemical Engineering, 2017)
Adsorption separation of phenol from aqueous solution using activated carbon was investigated in this work. The adsorbent was prepared from coconut shell and activated by physical activation method. The coconut shell was first carbonized at 800°C under nitrogen atmosphere and activated by CO2 at the same temperature for one hour. The prepared activated carbon was characterized by Scanning Electron Microscope (SEM) and BET Surface Analyzer and by the determination of iodine number as well as Boehm titration. The iodine number indicates the degree of relative activation of the adsorbent. The equilibrium adsorption isotherm phenol from aqueous solution was performed using liquid phase batch adsorption experiments. The effect of experimental parameters including solution pH, agitation time, particle size, temperature and initial concentration was investigated. The equilibrium data was analyzed using Langmuir and Freundlich adsorption model to describe the adsorption isotherm and estimate the adsorption isotherm parameters. The results indicate the potential use of the adsorbent for removal of phenol from the aqueous solution. Journal of Chemical Engineering, Vol. 29, No. 1, 2017: 9-13